Early childhood weight gain: Latent patterns and body composition outcomes. Issue 5 (7th May 2021) - Norris, Tom; Mansukoski, Liina; Gilthorpe, Mark S.; Hamer, Mark; Hardy, Rebecca; Howe, Laura D.; Li, Leah; Ong, Ken K.; Ploubidis, George B.; Viner, Russell M.; Johnson, William
Abstract: Background: Despite early childhood weight gain being a key indicator of obesity risk, we do not have a good understanding of the different patterns that exist. Objectives: To identify and characterise distinct groups of children displaying similar early‐life weight trajectories. Methods: A growth mixture model captured heterogeneity in weight trajectories between 0 and 60 months in 1390 children in the Avon Longitudinal Study of Parents and Children. Differences between the classes in characteristics and body size/composition at 9 years were investigated. Results: The best model had five classes. The "Normal" (45%) and "Normal after initial catch‐down" (24%) classes were close to the 50th centile of a growth standard between 24 and 60 months. The "High‐decreasing" (21%) and "Stable‐high" (7%) classes peaked at the ~91st centile at 12‐18 months, but while the former declined to the ~75th centile and comprised constitutionally big children, the latter did not. The "Rapidly increasing" (3%) class gained weight from below the 50th centile at 4 months to above the 91st centile at 60 months. By 9 years, their mean body mass index (BMI) placed them at the 98th centile. This class was characterised by the highest maternal BMI; highest parity; highest levels of gestational hypertension and diabetes; and the lowest socio‐economic position. At 9 years, the "Rapidly increasing" class was estimated to have 68.2% (95% confidence interval [CI] 48.3, 88.1) more fat mass than the "Normal" class, but only 14.0% (95% CI 9.1, 18.9) more lean mass. Conclusions: Criteria used in growth monitoring practice are unlikely to consistently distinguish between the different patterns of weight gain reported here.